2017
DOI: 10.4338/aci-2016-08-ra-0138
|View full text |Cite
|
Sign up to set email alerts
|

The effect of requesting a reason for non-adherence to a guideline in a long running automated reminder system for PONV prophylaxis

Abstract: In this study requesting a reason for non-adherence is associated with improved guideline adherence. The effect seems to depend on the underlying reason for non-adherence. It also illustrates the importance of human factors principles in the design of decision support. Some reasons for non-adherence may not be influenced by automated reminders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The potential limitation of guidelines and a contributing factor to PONV is the low adherence to protocol by providers. 2,17 Several studies suggest the importance of including clinical decision tools or hard stops as automated reminders in the electronic medical record. The use of hard stops requires providers to specify a reason for nonadherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential limitation of guidelines and a contributing factor to PONV is the low adherence to protocol by providers. 2,17 Several studies suggest the importance of including clinical decision tools or hard stops as automated reminders in the electronic medical record. The use of hard stops requires providers to specify a reason for nonadherence.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as increased workload, documentation error, and provider's disagreement with the validity of the risk score have been shown to result in providers' nonadherence and failure to appropriately document patients' risk scores. 17 The Society for Ambulatory Anesthesia (SAMBA) compiled evidenced-based guidelines to inform the current anesthesia practice on PONV management. 2,14 They recommend identifying patients at risk for PONV, identifying the most effective antiemetic single therapy and combination therapy regimens for PONV prophylaxis, the administration of two or more pharmacologic interventions for adults at high risk for PONV, ensuring that PONV prevention and treatment are implemented in the clinical setting, and the facilitation and use of multimodal PONV prevention guidelines and algorithms for surgical patients.…”
Section: Literature Reviewmentioning
confidence: 99%
“…5 Face validity of the formative construct is more credible, as both risk factors and appropriate antiemetic prophylaxis are uncontroversial. 65 Both reliability and construct validity remain to be evaluated in future research.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…10,11 High-quality clinical practice guidelines on PONV management have been developed, and they recommend prophylaxis administration based on PONV risk stratification. 3,8,12 However, their actual effects on clinical practice are limited [13][14][15][16] because of several reasons.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…9,14,16,20,30 Some studies attempted to improve clinicians' compliance with PONV prophylaxis through different interventions, 13,15,20,[30][31][32][33] among which automated reminders were most commonly reported. 13,16,31,33,34 However, the real role about automated reminders remains controversial and is limited in PONV management. 9,33 Kooij found that after discontinuation of automated reminders, guideline adherence decreases back to control levels.…”
Section: F I G U R Ementioning
confidence: 99%